Establishment of a formal program for retinoblastoma: Feasibility of clinical coordination across borders and impact on outcome. Issue 11 (18th August 2019) - Al‐Haddad, Christiane; Bashour, Ziad; Farah, Lina; Bayram, Layal; Merabe, Zeina; Ma'luf, Riad; Alameddine, Ramzi; Eid, Toufic; Geara, Fadi; Wilson, Matthew; Brennan, Rachel; Jeha, Sima; et al.
Abstract: Retinoblastoma is an ocular tumor that occurs in young children, in either heritable or sporadic manner. The relative rarity of retinoblastoma, and the need for expensive equipment, anesthesia, and pediatric ophthalmologic expertise, are barriers for effective treatment in developing countries. Also, with an average age‐adjusted incidence of two to five cases per million children, patient number limits development of local expertise in countries with small populations. Lebanon is a small country with a population of approximately 4.5 million. In 2012, a comprehensive retinoblastoma program was formalized at the Children's Cancer Institute (CCI) at the American University of Beirut Medical Center, and resources were allocated for efficient interdisciplinary coordination to attract patients from neighboring countries such as Syria and Iraq, where such specialized therapy is also lacking. Through this program, care was coordinated across hospitals and borders such that patients would receive scheduled chemotherapy at their institution, and monthly retinal examinations and focal laser therapy at the CCI in Lebanon. Our results show the feasibility of successful collaboration across borders, with excellent patient and physician adherence to treatment plans. This was accompanied by an increase in patient referrals, which enables continued expertise development. However, the majority of patients presented with advanced intraocular disease, necessitating enucleation in 90% of eyes in unilateral cases, and more than 50% of eyes in bilateral cases. Future efforts need to focus on expanding the program that reaches to additional hospitals in both countries, and promoting early diagnosis, for further improvement of globe salvage rates.